Emerging Technologies for Secure and Privacy-Preserving Electronic Medical Records: A Systematic Review - Putra, Muhammad Ifantara; Roziqin, Mochammad Choirur; Alfiansyah, Gamasiano (ILKOMNIKA, 2025)
The rapid digitalization of healthcare has led to widespread adoption of Electronic Medical Records (EMR), driving improvements in data management, clinical efficiency, and patient-centered care. However, this transformation also presents critical challenges related to data security, privacy protection, and intelligent data utilization. This study conducts a Systematic Literature Review (SLR) of 30 peer-reviewed journal articles published between 2022 and 2025, focusing on three key research domains: EMR systems, smart data processing, and blockchain-based security. The review identifies that EMR serves as the foundation for healthcare data standardization and interoperability, while smart data processing—through artificial intelligence and machine learning—enables predictive analytics and clinical decision support. Concurrently, blockchain technology strengthens data integrity, transparency, and access control in distributed medical environments. Despite these advances, persistent challenges remain, including scalability limitations, interoperability gaps, and ethical concerns in data governance. The study concludes that integrating blockchain with intelligent data processing represents a promising path toward developing secure, interoperable, and intelligent EMR systems capable of supporting the next generation of digital healthcare.